Bird Diversity of a Riparian Forest in the Nilgiri Biosphere Reserve, India - Manikandan, P.; Balasubramanian, P. (Indian Forester, 2016)
A total of 158 species of birds belonging to 56 families was recorded in a lowland riparian forest in along Bhavani river in the Nilgiri Biosphere Reserve, India from August 2012 to July 2014. Of the 158 species of birds, 110 species were residents, 33 were winter migrants and 15 summer migrants. The order Passeriformes was highest in dominance followed by Piciformes and Falconiformes. Insectivores (47%) constituted the most predominant guild followed by frugivores (20%). Highest species richness (127) was observed in February and lowest (75) in July. Maximum diversity value (4.23) was recorded in December. Avifauna of the study area comprised one threatened species, Nilgiri Woodpigeon (Columba elphinstonii)- Vulnerable and five near-threatened species and four endemic species. This study illustrated useful information on bird diversity of a low-land riparian forest which serves as a baseline for future research and monitoring.